PENGARUH BERMAIN JUMP NUMBERS TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN DI TK AGAPE KECAMATAN TAMPAN KOTA PEKANBARU - Sri Wahyuni; Zulkifli N Zulkifli N; Hukmi S Hukmi S (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of Playing Jump Numbers To Know Concept Number Ability Of Child Age 4-5 Years In TK Agape Tampan Sub District Pekanbaru City. The population in this study that children A classes totaling 18 children and sample in this study amounted to 18 children. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. This type of instrument used in this study is to use the observation and documentation to take notes about events that occurred during the treatment given. Based on the results obtained by testing the hypothesis that there are significant playing jump number To Know Concept Number Ability Of Child Age 4-5 Years In TK Agape Tampan Sub District Pekanbaru City. This known t count 13.52 or significance (0.000), because sig < 0.05, it can be concluded that there are differences in the ability to know concept number ability on students significant before and after using playing jump number in the learning. Hypothesis testing can be seen on t = 13.52 > table = 2,110. It has been suggested that there are significant differences in the results between the pretest and posttest. Plaing jump numbers to know concept number ability of child Age 4-5 Years In TK Agape Tampan Sub District Pekanbaru City amounted to 50,40 %.Keyword : Concept Number, Playing Jump Number